Assessing the therapeutic efficacy of Cefoperazone Sodium and Sulbactam Sodium in managing surgical site infections: a retrospective analysis - Ling Zhai; Peipei Wang (Scientific Reports)
Abstract Surgical site infections (SSIs) pose significant challenges in surgical care, impacting patient recovery and healthcare costs. The increasing prevalence of antibiotic-resistant bacteria necessitates effective antimicrobial strategies. This study assesses the therapeutic efficacy and safety of Cefoperazone Sodium and Sulbactam Sodium in managing SSIs and compares its effectiveness against a standard treatment. A retrospective analysis was conducted on 110 patients with clinically and microbiologically confirmed SSIs from December 2020 to December 2023. Patients were divided into two groups: 55 received Cefoperazone Sodium and Sulbactam Sodium, while 55 were treated with Cefuroxime. The efficacy was evaluated based on microbiological eradication and clinical improvement, assessed after 3 days of treatment. Statistical analyses were performed using SPSS version 27.0, with significance set at p < 0.05. Demographic and clinical characteristics showed no significant differences between groups, ensuring comparability. The observation group demonstrated a cure rate of 58.18% and an overall efficacy rate of 94.55%. In contrast, the control group showed a cure rate of 32.73% and an overall efficacy rate of 70.91%. Statistical analysis revealed a significant difference in therapeutic success between the groups (Chi-square value of 9.16, p-value < 0.05). The combination of Cefoperazone Sodium and Sulbactam Sodium could provide a more effective option for managing SSIs, potentially improving cure rates and overall treatment outcomes compared to Cefuroxime.